Prevalence of Psoriasis and Psoriatic Arthritis and Patient Perceptions of Severity in Sweden, Norway and Denmark: Results from the Nordic Patient Survey of Psoriasis and Psoriatic Arthritis - Kjersti Danielsen; Albert Duvetorp; Lars Iversen; Mikkel Østergaard; Oliver Seifert; Kåre Steinar Tveit; Lone Skov (Medical Journals Sweden, 2018)
Optimal clinical management of psoriasis and psoriatic arthritis (PsA) Optimal clinical management of psoriasis and psoriatic arthritis (PsA) requires understanding of the impact on patients. The NORdic PAtient survey of Psoriasis and PsA (NORPAPP) aimed to obtain current data on disease prevalence and patient perceptions in Sweden, Denmark and Norway. Among 22,050 individuals questioned, the reported prevalence of psoriasis and/or PsA was 9.7% (5.7% physician-diagnosed plus 4.0% self-diagnosed only); prevalence was similar in Sweden (9.4%) and Denmark (9.2%) but significantly higher in Norway (11.9%). Of those reporting a physician's diagnosis, 74.6% reported psoriasis alone, 10.3% PsA alone and 15.1% both. Patients with PsA perceived their disease to be more severe than those with psoriasis; patients with PsA and psoriasis reported greater disease severity than those with each condition alone. Patient's perceptions of psoriasis severity correlated weakly (Spearman's rho 0.42) with clinical severity; both patient perceptions and clinical measures are important in the assessment and management of psoriasis.